2022
DOI: 10.1155/2022/6071276
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated CoCoSo-CRITIC-Based Decision-Making Framework for Quality Evaluation of Innovation and Entrepreneurship Education in Vocational Colleges with Intuitionistic Fuzzy Information

Abstract: This paper proposes a multiattribute group decision-making (MAGDM) based on the CoCoSo method under the intuitionistic fuzzy sets (IFSs) environment for quality evaluation of innovation and entrepreneurship education (IEE) in vocational colleges. First of all, this paper extends the CoCoSo to the IFSs environment. Second, a new MAGDM model for quality evaluation of IEE in vocational colleges based on the CoCoSo algorithm is built. In this algorithm, the attribute weight is derived by subjective weight and obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Literature [12] stood in the vision of resource-based theory and studied how SMEs use active entrepreneurial behavior to accomplish new product development through survey analysis. Literature [13] establishes a quality evaluation model of innovation and entrepreneurship education in colleges and universities based on the CoCoSo algorithm and confirms the effectiveness of the CoCoSo algorithm in innovation and entrepreneurship education quality evaluation through the comparative analysis of algorithm performance. Literature [14] analyzed the relationship between innovation and entrepreneurship education and the survival rate of entrepreneurial projects during the seven-year period of 2010-2017 and concluded that innovation and entrepreneurship education do not have a significant impact on the survival rate of entrepreneurial projects, which is more reflected in innovation and entrepreneurial behavior.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Literature [12] stood in the vision of resource-based theory and studied how SMEs use active entrepreneurial behavior to accomplish new product development through survey analysis. Literature [13] establishes a quality evaluation model of innovation and entrepreneurship education in colleges and universities based on the CoCoSo algorithm and confirms the effectiveness of the CoCoSo algorithm in innovation and entrepreneurship education quality evaluation through the comparative analysis of algorithm performance. Literature [14] analyzed the relationship between innovation and entrepreneurship education and the survival rate of entrepreneurial projects during the seven-year period of 2010-2017 and concluded that innovation and entrepreneurship education do not have a significant impact on the survival rate of entrepreneurial projects, which is more reflected in innovation and entrepreneurial behavior.…”
Section: Introductionmentioning
confidence: 70%
“…Exploration of aesthetic education path for college students based on cognitive multi-method integration of innovation and entrepreneurship cultivation 13 2. This research was supported by the Jiangsu Qing Lan Project (2023).…”
Section: Fundingmentioning
confidence: 99%
“…Strengthen the teaching reform and training of innovation and entrepreneurship education teachers, supported by high-level innovation and entrepreneurship tutors, to enhance the innovation spirit, entrepreneurial awareness, and innovation and entrepreneurship ability of college students [5][6]. Innovation and entrepreneurship education in colleges and universities have entered the stage of transformation and development, and strengthening the construction of innovation and entrepreneurship teachers has become one of the core issues in deepening the reform of innovation and entrepreneurship education [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Vocational education is an important part of the national education system and human resources development, and an important way to train diversified vocational and technical talents and promote employment and entrepreneurship [1][2][3][4][5][6]. Improving the quality of education is the key to training vocational and technical talents.…”
Section: Introductionmentioning
confidence: 99%